Eficiencia agronómica de tres variedades de maíz (Zea mays l), producidos con semilla de tres secciones diferentes de la mazorca, en Laguacoto III, provincia Bolívar - Borja Ulloa, Mirian Janeth (2022)
The cultivation of soft corn in the highlands of Bolívar Province, which includes the cantons of Guaranda, Chimbo, San Miguel, and Chillanes, is of great importance in the components of the family economy. In Bolívar province, ignorance is one of the main factors that makes farmers not use all parts of the corn cob at the time of planting, excluding the part of the apex of the cob, for animal consumption. One of the main drawbacks, when consumers purchase corn, since they must have certain characteristics, such as thick and soft grain, in order to obtain a higher yield and better quality. Therefore, we will focus this research on the following objectives: Evaluate the main components of yield in the soft corn varieties INIAP -103, INIAP -111 and CHAZO. Determine the section of the cob that generates the highest yield in the cultivation of the three varieties of corn. Carry out an economic analysis of the B/C ratio. The present essay was carried out at the Laguacoto III Experimental Farm. Corn varieties were used; INIAP-111; INIAP-103 and CHAZO; with seeds obtained from the cob part; Apex; Medium and Base. A randomized complete block design was used in a factorial arrangement of 3 x 3 x 3 repetitions. (DBCA). Tukey tests at 5% were performed to compare the means of factors A; B and A x B interactions. Correlation analysis and linear regression. Economic analysis B/C cost-benefit ratio The main results obtained in this research were: The agronomic response of the three maize varieties was very different, with the highest yield being INIAP-103 (A2), which presented an average grain yield at 13% humidity with 5.750 kg/ha. A highly significant effect of the three different sections of the cob used for seed was determined, with the highest yield being B2 (middle section) with 4.975,81 kg/ha of dry corn at 13% moisture. The most important dependence of factors (varieties by sections of cob) was presented in the dry corn yield variable and the highest average corresponded to treatment T4 (A2B1): with 5.980,33 kg/ha at 13% humidity. The yield components that significantly increased corn yield were: Percentage of emergence in the field (PEC), Plant height (AP), Days to dry harvest (DCS), Survival percentage (PS), Percentage of # of plants with two ears (PNPCDM), yield per plot (R*P), ear diameter (DM) and ear length (LM). The independent variables that decreased performance were; stem lodging percentage (PAT) and root lodging percentage (PAR), this means that XXVI the higher the stem and root lodging, the lower the yield. Total net benefits ($/ha) highest in dry corn; it was presented by Q4 (A2B1) with $914,18 USD; and the highest benefit/cost ratio: RB/C of 1,38; with an RI/C of $0,38. This means that the producer, for every dollar invested, has a profit of $0,38.